Programmed ventricular stimulation for risk stratification in patients with myocardial scarring and an ejection fraction above or equal to 40%. (19th May 2022) - Soris, A; Herrera-Siklody, C; Lebloa, M; Domenichini, G; Teres, C; Porretta, A; Haddad, C; Pruvot, E; Pascale, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Sudden cardiac death (SCD) is one of the leading causes of death, particularly among patients with myocardial scars. Implantable cardioverter defibrillators (ICD) are recommended in patients with a left ventricular ejection fraction (LVEF) ≤ 35%. Another recognised indication is the induction of sustained ventricular tachycardia (VT) or ventricular fibrillation (VF) during programmed ventricular stimulation (PVS) in post-myocardial infarction patients with non-sustained VT and a LVEF between 35% and 40%. However, no recommendation exists to guide the use of prophylactic ICD implantation in patients with less altered LVEF, even though they represent the majority of SCDs. Purpose: We aimed to evaluate the prognostic value of PVS in patients with myocardial scars and a relatively preserved LVEF (≥ 40%). Methods: Patients with evidence of a chronic myocardial scar and a LVEF ≥ 40%, who underwent PVS at two hospital centers were considered for inclusion. Ischemic and non-ischemic myocardial scars were included. The primary endpoint was the occurrence of a Major Arrhythmic Event (MAE), namely SCD, clinical VT/ventricular fibrillation, or appropriate ICD therapy. Results: 134 patients were included (mean age 62.4 ± 12.5 years, LVEF 54.7 ± 8.6 %). Indication for PVS was mostly non-sustained VT and/or syncope (84%). Post-myocardial infarction patients represented about half of the cases (53%). Inducibility during PVS was observed in 17 patients (13%). There was a nonsignificant trend towards higher inducibility rates in ischemic versus nonischemic scars (17% and 8%, respectively; p-value = 0.1). Of these patients, 15 received an ICD (88%). Over a mean follow-up of 49 (±42) months, a MAE occurred in 7 patients (41.2%) with positive PVS, versus 4 patients (3.4%) with negative PVS. MAE-free survival at 10 years was 91% and 43% in PVS-negative and PVS-positive patients, respectively (p-value < 0.001). One SCD occurred in a PVS-positive patient who denied prophylactic ICD implantation. Inducibility during PVS provided a 64% sensitivity and a 97% negative predictive value (PV) to predict the occurrence of MAE (specificity 92%, positive PV 41%). Conclusion: PVS is a useful tool to discriminate patients with myocardial scars and LVEF ≥ 40% at increased arrhythmic risk. Effective utilisation of ICD may be anticipated in case of positive PVS, while non-inducible patients are at lower MAE risk.